Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 545515 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Fagus sylvatica L.", "HasCoordinate is true" ] } The dataset includes 545515 records from 793 constituent datasets: 1 records from Biosph?renpark Wienerwald - Pfaffst?tten. 41 records from Application INPN Esp?ces: Observations naturalistes, participatives et opportunistes, fond?es sur des photographies. 1592 records from Welsh BSBI data (ex-VPDB dataset) at hectad resolution. 1 records from Waldst?ck Bremerhagen LK Bio Kl. 12. 8 records from Steierm?rkisches Landesmuseum Joanneum - Herbarium GJO. 2 records from Trockenrasen und Buchenwald in der Umgebung der Jugendherberge Bad Blankenburg. 1 records from Kremmer Luch. 1 records from Bannwald Burghauser Forst. 23 records from Botany registration database by Danish botanists. 1 records from T?pinger Mischwald. 13 records from Carnet B Centre - lot 2012. 1 records from Frauenholz (Holzmaden). 19 records from Inventaire de la flore des Pyr?n?es-Atlantiques 2018. 1 records from Stadtgebiet (Dannenberg). 22 records from University of Vienna, Institute for Botany - Herbarium WU. 4 records from Feriendorf des Kreises Gro?-Gerau/Ober-Seemen. 1 records from Donn?es esp?ces - Expertise IPE 66. 2 records from Artenvielfalt des "Gr?nen Klassenzimmers". 1 records from Donn?es esp?ces Expertise IQE 311. 32 records from Colecci?n de plantas vasculares del Herbario "Jaime Andr?s Rodr?guez". LEB. 1 records from Waldsee. 1 records from Liether Park (LMS), 6c. 2112 records from Belgian IFBL Flora Checklists (1939-1971). 1 records from Vom Gipfel ins Moor, Transekt im NSG Allg?uer Hochalpen. 3 records from Donn?es naturalistes de l'Association BDEM. 4 records from Inventaire de la flore de Charente-Maritime 2015. 1422 records from Flora of Worcestershire. 1 records from Rund um das LUGY. 12525 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 1 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 2 records from Waldr?nder der Frankenh?he (Rothenburg ob der Tauber). 2 records from Collections of Bioclass, school #179, Moscow. 3 records from Species found in the NOMS estate 2005 - Present. 1 records from Schulgel?nde IGS Kaufungen. 27 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 1 records from privater Garten. 10 records from TransForest - vegetation, lichen and fungi data 2016. 21 records from Inventaire de la flore de Dordogne 2018. 6 records from Ektomykorrhizen auf VIP Alb (Wald). 1 records from Spielwiese. 1 records from Pflanzen und Tiere im Burgwald. 43 records from Biowide Species data. 1 records from ?rtzem?ndung (Stedden). 1 records from Überall ist Wunderland. 1 records from Bolzplatz. 1 records from Donn?es naturalistes de l'AGUPE (Association G?n?rale d'Urbanisme et de Protection de l'Environnement). 6 records from ?tude vallons froid - Parc naturel r?gional de Lorraine. 2 records from Landschaftsschutzgebiet Buchhorst 3. 2524 records from Scottish SNH-funded BSBI records. 2 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 2 records from VFD HH/SH "Pferdeweide Lemsahl". 972 records from Merseyside BioBank (verified). 1 records from Langenberger Forst am Ochsenweg/ Nieb?ll-Leck. 1 records from Schiller Gymnasium Hof 10b. 68 records from Inventaire de la flore de Dordogne 2017. 76 records from Donn?es naturalistes de Damien AVRIL. 12265 records from Observations du Conservatoire botanique national du Bassin parisien.. 1 records from katzenbuckel. 1 records from Innenh?fe der Gesamtschule Berger Feld/ Gelsenkirchen. 2 records from Biotope in Rheine - Aktion 350. 21326 records from Flora von Deutschland (Phanerogamen). 1 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 1 records from Inventaire de la flore de la Vienne 2014. 1 records from Bulau. 1 records from Liether Park 2 (LMS), Klasse 6c. 2 records from Faun. 2 records from Donn?es naturalistes de S?gol?ne FAUSTEN. 2 records from Natural History Museum Maastricht (NL) - Herbarium. 73353 records from Artportalen (Swedish Species Observation System). 9630 records from Observations floristiques issues de la base de donn?es du Conservatoire botanique national alpin. 24664 records from Floristic records from survey studies of the Bayerisches Landesamt f?r Umwelt. 1 records from Wassermann. 97 records from Vascular Plants, Field notes, Oslo (O). 1 records from Gel?nde des Schulzentrums am Himmelsbarg. 677 records from The Fungal Collection of Helga Gro?e-Brauckmann at the Botanische Staatssammlung M?nchen. 1 records from K?nigsdorfer Wald. 302 records from Wikiplantbase #Toscana. 1 records from Artenf?lle um das Schalkenmehrener Maar. 82 records from BioFokus. 41 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 4 records from Inventaire du Lac de Marcenay (Bourgogne). 1 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 15 records from Anymals+plants - Citizen Science Data. 3 records from Donn?es naturalistes d'Oc?ane ROQUINARC'H. 10 records from Herbarium Universitatis Daugavpiliensis. 1 records from Lassentiner Moor (Niepars). 1 records from Rechts des Inn H?he Hofau Rosenheim. 1 records from Rund um den Hainbergsee. 3 records from International Barcode of Life project (iBOL). 1 records from LBV 100 - Artenvielfalt am Rothsee. 8 records from Estonian University of Life Sciences. 1 records from Ortelsbruch - Hangmoor bei Morbach. 7 records from Donn?es d'expertise convention GTM B?timent et le Service du patrimoine naturel du MNHN. 1 records from Waldfl?che im Natur-Erlebnis-Pfad Pfinztal. 164 records from Donn?es naturalistes d'Olivier ESCUDER. 4 records from River Pant historic river corridor surveys. 1 records from 20 Jahre Naturschutzgebiet Dreienberg. 23 records from Finnish Floristic Database (Finnish Museum of Natural History Collections). 4 records from Shire Group IDB species data 2004 to present. 12 records from Inventaire de la flore de Gironde 2018. 1 records from Frau Voss. 290 records from Observations occasionnelles Parc national des Pyr?n?es. 27 records from Moscow University Herbarium (MW). 1 records from Inventaire de la flore du PNRLG 2017 (Landes). 340 records from Base de datos de plantas vasculares del Pa?s Vasco: ARAN-EH. 219 records from National Plant Monitoring Scheme - England, Scotland, Wales. 1 records from WildesMoor bei Schwabstedt. 19 records from The Erysiphales Collection at the Botanische Staatssammlung M?nchen. 1 records from Naturparadies in Gr?fenhausen am Trifels (bei Annweiler). 1 records from Fliegenhaupt Marksuhl. 213 records from Dorset Sites of Nature Conservation Interest (SNCI) species records 2000-2008. 1 records from Garten J. Scherrer (Lachen-Speyerdorf). 1 records from Donn?es esp?ces - Expertise IPE 77. 21 records from IBF Monitoring of Fungi. 64 records from Inventaire de la flore de Dordogne 2015. 3 records from Estonian Museum of Natural History. 1 records from Donn?es esp?ces -Expertise IPE 76. 1 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 4 records from Naturerlebnisraum Koppelsberg. 2 records from Casual records for Scottish Wildlife Trust reserves - Verified data. 1 records from Artenvielfalt Kreis Gie?en. 6 records from Jeu de donn?es convention Eurovia-SPN-2012-2016. 1 records from Wiese am Waldrand (Gurtweil). 2 records from Renaturierung Werse (Innenbereich Beckum). 1 records from Liether Park (LMS), 5a. 1 records from Vascular Plants, Observations, Oslo (O). 3 records from UTEP Plants (Arctos). 4 records from Inventaire de la flore de Charente-Maritime 2016. 1 records from Naturpark Dr?mling. 6 records from RNF - Donn?es de la Communaut? de Communes de Gevrey Chambertin. 4 records from Photographs of higher plants, mosses, fungi, lichens, and algae. 2 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrh?bel" Chemnitz. 8 records from South Lanarkshire peatland records 2013. 36 records from Heritage Trees of Ireland. 16 records from SBT-Living. 1 records from Balkon (Norderstedt). 8 records from Donn?es esp?ces - Expertise IQE 92. 2 records from OBI - Robert F. Hoover Herbarium, Cal Poly State University. 7 records from Inventaire de la flore de Lot-et-Garonne 2014. 1 records from Inventaire de la flore de Charente-Maritime 2018. 4 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 51 records from Pollen profile RAC20, Lake Racou, France. 1 records from Lillachtal mit Kalktuffquelle bei Wei?enohe. 1 records from Zuk?nftiges NSG H?ftland/Bockholmwik. 5 records from Donn?es naturalistes de Lo?c SALAUN. 1 records from VSN-Wiese. 73 records from Wikiplantbase #Liguria. 1 records from Donn?es esp?ces - Expertise IPE 12. 1 records from Wulfsmuehle/Pinnau. 1 records from Umgebung der Gesamtschule Winterhude (Hamburg). 1 records from Donn?es de la base Ecosph?re. 10 records from Local BioBlitz Challenge 2013. 1 records from Triebesbach (Zeulenroda-Triebes). 10567 records from Other BSBI Scottish data up to 2014. 1 records from Donn?es naturalistes acquises sur les sites du MNHN. 49 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 1 records from Donn?es naturalistes de Wilfried RATEL. 18 records from Aranzadi Zientzi Elkartea. 20916 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 1 records from Wiese und Weide am Waldrand von Gusterath. 1 records from NSG Berschau - Auengebiet (Neustadt / Wied). 1 records from Unna-M?hlhausen, Wiesen. 21 records from IBF Monitoring of Plant Galls. 254 records from Isle of Man historical wildlife records 1990 to 1994. 5 records from Donn?es naturalistes de Julien BIRARD. 1 records from Donn?es esp?ces - Expertise IQE 52. 164 records from TWIC Biodiversity Field Trip Data (1995-present). 1 records from Donn?es naturalistes de LE GLOANEC Vincent. 31 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 1 records from KARSTLANDSCHAFT S?DHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am R?seberg). 962 records from Natural Resources Wales Regional Data : Mid-Wales. 1 records from Au?enfeuerstelle K?nigsbol (Hartheim/Me?stetten). 1 records from Wirbach. 126 records from River Biologists' Database (EPA). 881 records from Tiroler Landesmuseum Ferdinandeum. 12269 records from Collections and observation data National Museum of Natural History Luxembourg. 1 records from MPUC - Herb?rio do Museu da Pontif?cia Universidade Cat?lica do Rio Grande do Sul. 48 records from Natural History Museum, Vienna - Herbarium W. 1 records from Donn?es naturalistes de Pascal REVAULT. 3 records from University of British Columbia Botanical Garden Collections (UBCBG). 1 records from Inventaire de la flore du PNRLG 2018 (Landes). 142 records from Merseyside BioBank (unverified). 157 records from NBIS Records to December 2016. 1 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1 records from EURISCO, The European Genetic Resources Search Catalogue. 4006 records from Donn?es ONF faune-flore-fonge. 13 records from Stoke-on-Trent Environmental Survey results (1982-1984). 5 records from The New York Botanical Garden Herbarium (NY). 59 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Plantae. 1 records from B?G. 1 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 2 records from LOB - California State University, Long Beach Herbarium. 4 records from Inventaire de la flore de Gironde 2015. 1 records from Steinbruch Mainz-Weisenau, 2. Jahr. 8 records from Geneva Herbarium ? General Collection (G). 40 records from Donn?es acquises via le r?seau du Conservatoire botanique national du Bassin parisien. 1 records from Gr?nes Germersheim. 17 records from RNF - Donn?es du Conservatoire d'espaces naturel Franche-Comt?. 1 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 1 records from Orchideenstandort Nostengraben - Kretzberg (O?maritz). 1 records from Aktion - Friedensburg Oberschule. 1 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 1794 records from Floristische Kartierung ?sterreichs - Mapping the Flora of Austria. 1 records from Erlengraben/Lipp-Tal (?stringen). 10 records from Donn?es naturalistes de Philippe GOURDAIN. 9 records from Inventaire de la flore des Landes 2017. 1 records from Nationalpark Jasmund. 3 records from EDIT - ATBI in Gemer area (Slovakia). 1 records from Schulwald Marksuhl. 13 records from Natural History Museum (London) Collection Specimens. 1 records from AKG-Gel?nde (Bensheim). 2 records from Schule Sulzbach (Oberegg). 1 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 262 records from Online Atlas of Vascular Plants 2012-2020. 7 records from Jordal. 28908 records from Flore du Bassin parisien (CBNBP). 1 records from Artenvielfalt im Rhein-Neckar-Raum. 1 records from F?rderzentrum Schm?lln. 1 records from Lebensraum Gesamtschule (Langerwehe). 43 records from Inventaire de la flore de Lot-et-Garonne 2015. 2 records from Herbarium of Namur. 1 records from NSG H?lenbuch H?rnle (Tieringen/Me?stetten). 7453 records from Observations floristiques - plateforme SINP r?gionale SILENE PACA. 1 records from Urwald 1 (Bad Waldsee). 1 records from Schulhof und Anlagensee in Nellingen. 8 records from National Plant Monitoring Scheme - Northern Ireland. 2 records from Von Elf bis Elf" Der Botanische Garten Wuppertal. 1 records from Paul-Gerhardt-Schule Dassel. 1 records from Tag der Artenvielfalt im Taubental. 23275 records from Dutch Vegetation Database. 22 records from The Fungal Collection at the Botanische Staatssammlung M?nchen. 2 records from Phanerogamic Botanical Collections (S). 2 records from Dalbekschlucht. 1 records from Kindervilla Aussengel?nde/ Hiltroper Park. 1 records from Kohlstattbrunnental. 1 records from NABU-Projekt (Osterode am Harz) S?dharzer Gipskarst. 1 records from Xiloteca del IANIGLA (IANIGLA-CCT CONICET Mendoza): XIAM.. 2 records from Liether Park (LMS), 6g. 1 records from University of Florida Herbarium (FLAS). 1 records from W?lder im Hainbachtal. 1 records from Kindergarten. 46 records from Donn?es naturalistes de RAYNARD Philippe. 1 records from Collection plants of Sochi park "Dendrarium". 1 records from Donn?es esp?ces - Expertise IPE 11. 2 records from Langes Tannen(LMS), Klasse 5d. 208 records from Meise Botanic Garden Herbarium (BR). 9 records from GRT gaz inventaire Parc naturel r?gional de Lorraine. 92 records from Patrick Roper?s Notebooks. 22 records from Donn?es naturalistes de David HAPPE. 1 records from Artenvielfalt auf Restbauernhof. 1 records from Tag der Artenvielfalt mit Sch?lerInnen des Europa-Gymnasiums in W?rth am Rhein. 1 records from Mauervegetation,Flechten und anderes. 1 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 2 records from Feriendorf des Kreises Gro?-Gerau Ober-Seemen/Gedern. 1 records from Lustadter Wald .. 1 records from Botanischer Garten (Saarbr?cken). 1 records from GEO Biodiversity Day. 1 records from Manx Biological Recording Partnership UNVERIFIED Isle of Man records between 14/02/2017 and 05/09/2019. 2 records from The Myxomycetes Collections at the Botanische Staatssammlung M?nchen - Main Collection. 1 records from Klutensee. 34 records from Herbarium Berolinense, Berlin (B). 8 records from Galls on Beech Trees in Hainich, 2008. 188 records from Carnet B Lorraine. 1110 records from Fungus Collections at Staatliches Museum f?r Naturkunde Karlsruhe (Herbarium KR). 4 records from Donn?es naturalistes de GAULTIER Cyrille. 1 records from Klimaoasen in K?ln. 1 records from Klasse 3a. 1 records from PAMP-tracheo: Vascular plants in Pamplona Basin (Navarra, Spain). Undergraduate thesis, D. Vicente. 1 records from Bodenseeufer Radolfzell. 1 records from Naturpark Kottenforst-Ville 19.6.09. 2 records from Inventaire de la flore de Gironde 2016. 3 records from Inventaire de la flore des Landes 2016. 5 records from Donn?es naturalistes de CERCOPE (Jean-Louis PRATZ). 1120 records from SER Site-based Surveys. 1 records from renaturierter Main (Kemmern bei Bamberg). 6 records from Atlas de la flore de Lorraine. 1 records from Quarrendorfer Landschaftsschutzgebiet. 53 records from Vascular plant herbarium TRH, NTNU University Museum. 143 records from Oskarshamn herbarium (OHN). 1 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 2 records from Herbarium specimens of the Mus?um d'Histoire Naturelle of Aix-en-Provence (AIX). 176 records from Donn?es faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 2 records from DIBA-Parc del Montnegre i el Corredor. 5 records from MoJ BioBlitz August 2018. 1 records from Werl macht sich auf die Suche. 2 records from The Erysiphales Collection at the University Halle-Wittenberg. 6 records from Herbario ABH (Universidad de Alicante). 1 records from Donn?es esp?ces - Expertise IPE 62. 1 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 1 records from Perchtoldsdorfer Heide. 1 records from Tidlig oppdagelse og varsling av fremmede arter 2019. 1 records from Neckartals?dhang (Horb). 1 records from LK 11 im M?nchspark. 4 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung M?nchen. 9 records from Inventaire de la flore de Charente-Maritime 2017. 3483 records from RECORD Vascular Plant Data. 1 records from Mooswald (Freiburg). 1 records from CommunicA Koblenz - Wildkr?uterexkursion - Rheinsteig Bornhofer H?he. 28 records from Donn?es naturalistes de Cyril EPICOCO. 4 records from SJSU - Carl W. Sharsmith Herbarium, San Jose State University. 2 records from NDFF Wall Plants Monitoring Program. 2 records from Lebensraum Stadt und Park. 1361 records from Norwegian Species Observation Service. 1 records from Blumenrather Heide / Virneburg. 2 records from Donn?es naturalistes de Pascal Dupont. 14 records from Naturalis Biodiversity Center (NL) - Botany. 41 records from Inventaire de la flore des Pyr?n?es-Atlantiques 2016. 33049 records from Relev?s floristiques du protocole de l'Inventaire National Forestier de l'IGN. 2 records from Stadtpark Sulzbach-Rosenberg. 2 records from Umgebung der Gesamtschule Hamburg-Winterhude. 160 records from Donn?es Vigie-Flore. 186 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 1 records from BUND - Dassower See (L?beck/Dassow). 29 records from Inventaire de la flore des Landes 2015. 3 records from Herbario de la Universidad de Sevilla. 1 records from Finnish Floristic Database (Small Collections). 1 records from Schulwald Grundschule Br?gge. 11 records from Tropicos Specimen Data. 204 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Occurrence data from various smaller projects in Norway. 4 records from Schulzentrum "Parc Hosingen". 1 records from Cuxhavener K?stenheiden. 2840 records from BRERC species records from all years at full resolution excluding Notable Species within the last 10 years. 6 records from National Wetland Inventory (NV). 2 records from Hatikka Observation Database. 11 records from inatura - Erlebnis Naturschau Dornbirn. 9 records from CONN. 1425 records from Observations faune et flore du Parc national des ?crins. 171 records from DIBA-Parc Natural del Montseny. 2 records from "Schlechteberg" Ebersbach/Sa.. 4 records from Silbertor + Wasserbachtal (Rutesheim / Renningen). 1 records from Knechtweide (Kohlfurth). 2 records from Nijmegen Natural History Museum (NL) - Herbarium. 1373 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 1 records from Dierloch, n?rdlicher Mooswald (Freiburg-Hochdorf). 1 records from Natura 2000 Parc naturel r?gional de Lorraine. 1 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 1 records from Collection botanique Le Grand A. (BOUM). 1 records from Naturpark Kottenforst-Ville 18.6.09. 1 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 2 records from R?mertal (Steinpleis). 1569 records from Atlas Flora Danica. 5 records from BoBO - Botanic Garden and Botanical Museum Berlin Observations. 11 records from Inventaire du legs Th?nard (Bourgogne). 1 records from Schlattstaller Tal (Lenningen). 10 records from Ektomykorrhizen auf VIP Hainich (Wald). 1 records from Naturpark Kottenforst-Ville 15.6.09. 1 records from Roter Berg Werdau (Leubnitz). 5 records from Finnish Floristic Database (Literature Sources). 5462 records from naturgucker. 7 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 2574 records from iNaturalist Research-grade Observations. 1 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 1 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 252 records from Environmental Monitoring Database Species data 1987 to 2015. 1 records from Donn?es naturalistes de PONCET R?my. 7 records from Botany Division, Yale Peabody Museum. 17 records from Donn?es naturalistes de Pascal AMBLARD. 1 records from Donn?es esp?ces - Expertise IPE 33. 1 records from Artenerfassung f?r Jedermann in der Grundschule Kirchboitzen. 2 records from Stadt K?nigs Wusterhausen. 2 records from Freiburger GEO-Tag der Artenvielfalt. 1 records from Tiergarten (Zeitz). 3 records from HO AVH data. 27 records from Colecci?n de plantas vasculares del herbario de la Universitat de Val?ncia (VAL). 1 records from W?lder bei Nordkirchen. 3 records from Wikiplantbase #Sardegna. 1 records from Wedeler Au. 1 records from Mi?mahlsche Anlage. 4 records from Vascular plants of Amrum 2007-2008. 2 records from InboVeg - NICHE-Vlaanderen groundwater related vegetation relev?s for Flanders, Belgium. 1 records from K?stenschutzwald. 1 records from Donn?es esp?ces -expertise IQE 3. 2 records from Field Museum of Natural History (Botany) Seed Plant Collection. 1 records from M?nchspark. 25 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 3 records from Jeux de donn?es provenant de l'ATBI Mercantour. 1 records from Gewann Krampf (Heilbronn). 2 records from FFH-Gebiet "Calwer Heckeng?u". 14 records from Inventaire de la flore des Pyr?n?es-Atlantiques 2017. 12 records from Auckland Museum Botany Collection. 1 records from Sahrbachtal Kreis Ahrweiler. 1 records from Industriebrache (Kempen). 8 records from Inventaire de la flore des ENS des Pyr?n?es-Atlantiques 2011-2012. 1 records from L?ner Holz (L?neburg). 45 records from Donn?es naturalistes de Pierre DUFRENE. 1 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 3 records from Inventaire de la flore de Charente 2013. 1 records from Schulgel?nde IGS-Frosch (Thaleischweiler-Fr?schen). 1 records from Schulgarten mit Klasse 8a (Essen). 344 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 12 records from Universidad de Oviedo. Departamento de Biolog?a de Organismos y Sistemas: FCO. 1 records from Philosophenwald und Wieseckaue in Gie?en. 2 records from University of Vermont, Pringle Herbarium. 1 records from Wald am Schloss Wittgenstein Bad Laasphe. 43 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 203 records from The DNA and Sample Repository at AIT. 27 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1 records from Herbario de Plantas Vasculares de la Asociaci?n BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 3309 records from FLORIVON. 93 records from Lothian Wildlife Information Centre Secret Garden Survey. 545 records from Flora of the Sto?owe Mts.. 1 records from Streuobstwiese Stedar 2009. 1 records from Stabbetorp - Floristiske registreringer 2016. 1018 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 6685 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 59 records from Donn?es faune, flore et fonge du Conservatoire des espaces naturels du Nord Pas-de-Calais. 1 records from Flusswerder in der Weser (Hameln). 2 records from Rund um den Eichwald,Schulhof Friedrich Fr?bel Gymnasium- Bad Blankenburg. 1 records from R?ckkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 1 records from Bayerische Donau - Blindheim Donaubr?cke. 1 records from Waldst?ck am Schullandheim Bad Bederkesa. 4 records from Inventaire de la flore du Grand Poitiers 2009. 1 records from M?hlenbach bei Buxtehude. 1 records from Unser Schulhof. 1 records from Schulhof Gymnasium H?rth Bonnstrasse. 1 records from Gronau - auf der Suche nach dem Neunauge. 1 records from Landschaftsschutzgebiet Buchhorst 4. 2 records from Gesch?tzter Landschaftsbestandteil - GLB "Troppach". 8415 records from Observations floristiques flout?es issues de la base de donn?es flore du Conservatoire botanique national alpin. 1 records from Schulgel?nde Gebr?der-Grimm-Schuleund Umgebung (Lingen). 1 records from Donn?es naturalistes de Jeanne VALLET. 12 records from Finnish Floristic Database (University of Turku Collections). 4 records from Herbario de la Universidad P?blica de Navarra, Pamplona: UPNA-H. 162 records from Vascular Plant Herbarium, Oslo (O). 5 records from Kathryn Kalmbach Herbarium. 615 records from Vascular Plant Records up to 2010. 21 records from Inventaire de la flore des Landes 2012 (Chalosse et Tursan). 31 records from The Lichen Collection at the Botanische Staatssammlung M?nchen. 1 records from Wald und Wiese am Buchwald. 2 records from Inventaire de la flore de Charente-Maritime 2012. 1 records from Finnish Floristic Database (?bo Akademi University Collections). 873 records from Donn?es d'occurrences Esp?ces issues de l'inventaire des ZNIEFF. 1 records from D?chtb?hlwald (Bad Waldsee). 11 records from IBF Monitoring of Lichens. 6 records from PlutoF platform observations. 343 records from Donn?es naturalistes flore et fonge du Conservatoire des espaces naturels Auvergne saisies avant le 18 f?vrier 2019.. 53 records from RNF - Donn?es du Conservatoire d'espaces naturel Limousin. 1017 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 11 records from Manx Biological Recording Partnership VERIFIED Isle of Man records between 14/02/2017 and 05/09/2019. 1 records from Herbario de Universidad de Murcia: MUB. 11 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 1 records from GEO-Hauptveranstaltung (Insel Vilm). 4 records from Geographically tagged INSDC sequences. 23 records from WTSWW Data: All Taxa (West Wales). 1 records from Donn?es esp?ces - Expertise IQE 88. 1 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 1 records from K?hmark bei Wetzlar. 1 records from F?rstenberger Ralley Teil 3. 1 records from Aachtobel. 10 records from Karplanter i vernet barskog og edell?vskog. 1 records from Schlichemquelle (Tieringen/Me?stetten). 6 records from Water Colours of Fungi by Konrad Schieferdecker at the Botanische Staatssammlung M?nchen. 25 records from Modernisation des ZNIEFF du PnrL. 1 records from Donn?es naturalistes de Martin HILAIRE. 1 records from Donn?es esp?ces - Expertise IQE 38. 1 records from Universit?t Salzburg. 1 records from Lebensraum Walram. 1 records from Stadtbiotop Ulrichteich. 1 records from Donn?es esp?ces - Expertise IPE 23. 1 records from TBW-Schafberg. 1 records from Kurler Busch (Scharnhorst). 23 records from Donn?es naturalistes de Xavier JAPIOT. 1 records from Umgebung von Schorndorf. 2 records from BioFresh Pond Data. 2 records from ?kostation (Freiburg). 1 records from Ludwigshofen. 1 records from Unser Schulhof - eine Apotheke. 1 records from Inventaire de la flore de Charente-Maritime 2014. 114 records from All taxa records for Leicestershire and Rutland. 1 records from DJH. 2 records from Expedition "Schulgel?nde". 1 records from Gemeindegebiet Weikendorf (Marchfeld). 1 records from Naturschutzgebiet Bausenberg. 1 records from Berlin - Treptower Park / Karpfenteich. 1 records from GEO Hauptveranstaltung Tirol (Innsbruck). 207 records from Cat?logo Flor?stico Hist?rico de Navarra. Gobierno de Navarra. 1 records from Stausee (Oberdigisheim/Me?stetten). 11 records from Natural History Museum Rotterdam - Specimens. 1 records from Artenvielfalt in der Kinderakademie im RFZ. 2 records from Naturgarten Langenholtensen. 1 records from Erzental (Oberotterbach). 1 records from Schwanheimer Wald. 23 records from National System of Protected Areas in Poland - Plants. 1 records from Listhof und Umgebung. 1 records from AKG-Bensheim. 1 records from Wupperaue bei Kemna (Wuppertal). 1 records from Schloss Fasanerie Eichenzell. 6 records from Universidad de Oviedo. Departamento de Biolog?a de Organismos y Sistemas: FCO-Briof. 3 records from New Zealand Biodiversity Recording Network. 1 records from Rosarium (LMS), Klasse 6a. 24 records from Herbarium Senckenbergianum (FR). 172 records from Merseyside BioBank Active Naturalists (unverified). 3 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 1 records from Feldweg Waldkirchen. 8 records from ArtenFinder. 18 records from Inventaire et suivis d'esp?ces dans le Parc national des C?vennes. 1 records from Prophetensee Quickborn. 6 records from Species within North Ayrshire from 1984 - Present. 1 records from Die Teiche im Britzer Garten. 1 records from Herbario de la Facultad de Farmacia de la Universidad Complutense de Madrid (MAF). 1 records from S?dpark (Bochum-Wattenscheid). 8 records from NINA botanical collection. 3 records from Natural History Museum, University of Tartu. 12 records from RNF - Donn?es de l'association Vivarmor Nature. 197 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 1 records from Pottundkopp. 1 records from Dreilinden Gymnasium-Schulgel?nde. 79 records from fundiv france database. 1 records from City of Edinburgh Natural Heritage Service - Natural Heritage Service Data. 5 records from Inventaire de la flore des Landes 2018. 18 records from Radnorshire Wildlife Trust records held by BIS. 1 records from Landschaftsschutzgebiet Schmutterwald. 53 records from Donn?es naturalistes de Thomas GAILLARD. 1 records from Kloster Eberbach. 2 records from Tag der Artenvielfalt. 1 records from Schulinnenh?fe (Gelsenkirchen). 1 records from Feriendorf des Kreises Gedern (Ober-Seemen). 1 records from inventaire botanique et lich?nologique de D. HAPPE. 4 records from The Wildlife Information Centre - BioBlitz Events. 2 records from Sbp-BioBlitz2017_60years-BiodiversityData. 5401 records from Donn?es de la flore d?Alsace (SBA). 1 records from PAMP-tracheo: Vascular plants in La Demanda and Cameros mountain ranges (La Rioja, Spain). PhD project, L.M. Medrano. 702 records from National Trust Species Records. 2 records from Schlo? T?rnich (Kerpen). 1 records from Arteninventar rund um den Rannahof. 7 records from Wikiplantbase #Sicilia. 93 records from NRW Regional Data: North Wales. 1 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 5595 records from LERN Records. 1 records from P?hlberg bei Annaberg. 748 records from Miscellaneous records held on the Cofnod database. 1 records from Liether Park 1 (LMS), Klasse 5b. 9 records from iRecord Surveys. 13290 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 392 records from Phase 2 Woodland Survey of Wales. 895 records from Flore du Limousin. 5021 records from Flore Franco-Belge. 1 records from Sonnentaugemeinschaft. 3759 records from Sistema de Informaci?n de la vegetaci?n Ib?rica y Macaron?sica. 6722 records from Observation.org, Nature data from the Netherlands. 1 records from Donn?es esp?ces - Expertise IQE 308. 1 records from Donn?es esp?ces - Expertise IQE 95. 93 records from Inventaire de la flore des Pyr?n?es-Atlantiques 2015. 1 records from Gym Freyung. 1 records from Biosph?renpark Wienerwald - Wiener Steinhofgr?nde. 2 records from vegetation releves on grassland gridplots in 2007. 90 records from Biologiezentrum Linz. 1 records from NSG Dellwiger Wald, Dortmund. 2 records from Vascular plant herbarium, Troms? Museum. 14 records from Herbarium of the Department of Natural Forests (Forest Research Institute) - Plants. 1 records from Artenvielfalt auf dem Schulgel?nde. 1 records from Weinberg Reichersdorf. 1020 records from Gloucestershire Historic Wildlife Sightings prior to 1st Jan 2000. 4 records from Convention Suez Environnement (SITA) ? SPN. 392 records from Miscellaneous records held by BIS. 3 records from 500,000 plant Specimens from PE Herbarium in China from 1950 to 1999. 17 records from Jard?n Bot?nico de C?rdoba: Herbarium COA. 21 records from Wikiplantbase #Italia. 2 records from E. C. Smith Herbarium (ACAD) - Cape Breton University Collection. 1 records from Baggerseen bei Krauchenwies. 3 records from Norwegian Biodiversity Information Centre - Other datasets. 6353 records from Spatially explicit database of tree related microhabitats (TreMs). Version 1.2. Integrate+ project. 1 records from Werrem?ndung im Schwarzatal. 34 records from Inventaire de la flore des Pyr?n?es-Atlantiques 2014. 1 records from Langes Tannen (Uetersen). 1 records from Feriendorf Ober-Seemen. 1 records from Langes Tannen. 1 records from Bergkamen- Bergehalde Gro?es Holz. 7 records from Churchyards for London. 1 records from Flora d'Andorra. 1 records from Inventaire de la flore de Lot-et-Garonne 2016. 47 records from Data from Defra Family Organisations supplied to Staffordshire Ecological Record. 1 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 299 records from The vascular plants collection (P) at the Herbarium of the Mus?um national d'Histoire Naturelle (MNHN - Paris). 1 records from Standing Waters Database - Scotland. 1 records from Schulgarten-St.-Georg-Gymnasium. 1 records from GymnQuerfurt. 3132 records from SEWBReC Vascular Plants (South East Wales). 2 records from "Schwarzes Teich" (Waldpark Radebeul). 4488 records from Tercer Inventario Forestal Nacional. Ministerio de Agricultura, Alimentaci?n y Medio Ambiente (Espa?a/Spain). 49 records from Pollen profile RAA37, Lake Racou, France. 64 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 2 records from Donn?es naturalistes de Pierre NOEL (pnoel). 3692 records from Waarnemingen.be - Plant occurrences in Flanders and the Brussels Capital Region, Belgium. 1 records from Wiesen-W?lder-Wasser um Dansenberg, Biosph?renreservat Pf?lzerwald. 31 records from Fragment size of individual Fagus sylvatica trees based on microsatellite markers. 1 records from Wir erkunden die Hofau, Klasse 5c. 71 records from Inventaire de la flore de Dordogne 2016. 5 records from Allan Herbarium (CHR). 5 records from Eppingen und Umgebung. 8 records from Inventaire de la flore des Landes 2014. 1 records from Westerw?lder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 1 records from Donn?es d'occurrence Esp?ces issues de la base Natura 2000 : esp?ces d'int?r?t communautaire et autres esp?ces remarquables renseign?es dans les FSD. 5 records from Donn?es naturalistes de Paul ROUVEYROL. 2 records from Herbarium of University of Bia?ystok - Vascular Plants. 1 records from Von der Nutzung zur Natur. 1 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 1 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 1 records from Liether Park (LMS), 6b. 1 records from NSG Karwendel. 1 records from Streuobstwiese Stedar 2008. 1 records from VFD-BW, Linzgau: Pferdeweiden Neuweiler Hof. 1 records from Rund ums Schulgel?nde. 1693 records from CSIC-Real Jard?n Bot?nico-Anthos. Sistema de Informaci?n de las Plantas de Espa?a. 1 records from Alter Kreidebruch Sa?nitz/R?gen. 14 records from Conventions d??tude sur la biodiversit? fran?aise ? Partenariats du Service du patrimoine naturel. 1 records from PAMP-tracheo: Vascular plants with pharmaceutical use in Navarra (Spain). PhD project, S. Akerreta. 47 records from Brecknock Wildlife Trust (Now WTSWW Brecknockhire) records held by BIS. 22 records from Taxon occurrence data for the FungalRoot database. 17 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 1 records from Alter N?rdlicher Friedhof (M?nchen). 3 records from Donn?es naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 1 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 45 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 3 records from Inventaires et sciences participatives de l'ABT de l'Est Cantal. 1 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 71 records from Leicestershire and Rutland Mature trees Inventory 2011. 1712 records from TAXA - Flore et habitats naturels de Franche-Comt?. 3 records from Donn?es diverses du Parc naturel r?gional de Lorraine. 1 records from Royal Ontario Museum Green Plant Herbarium (TRT). 117 records from Montgomeryshire Wildlife Trust records held by BIS. 1 records from Tag der Artenvielfalt in Heidelberg. 7 records from NMNH Extant Specimen Records. 1 records from Bioimages. 49 records from Donn?es RNF - PNR des ballons des Vosges. 1 records from Naturschutzgebiet Sistig-Krekeler-Heide. 1 records from Isartal Dingolfing. 2 records from "Schwarzwassertal" bei Pobershau. 1648 records from FloraCAT: Banco de datos de los corm?fitos de Catalu?a. 1 records from Biotope auf dem Gel?nde der Eggerstedt- Kaserne in der Nachbarschaft der Theodor-Heuss-Schule. 1 records from Questagame weekly feed. 12 records from Donn?es naturalistes de Cyrille DELIRY. 2 records from Vascular Herbarium, NMBU. 33 records from Donn?es Herbiers de l'Universit? de Strasbourg. 390 records from Donn?es acquises dans le cadre de l'activit? du bureau d'?tude BIOTOPE (1994 - 2013). 1 records from Danielsberg (M?lltal, K?rnten). 3 records from Biodiversity4all Research-Grade Observations. 1 records from Naturpark Kottenforst-Ville 17.6.09. 1 records from Donn?es esp?ces - expertise IQE 110. 1 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 2 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 66652 records from INPN - Donn?es flore des CBN agr?g?es par la FCBN. 22 records from Bryophytes, fungi and lichens on dead wood. 1 records from Insektenvielfalt Ahe/Weichelsee. 73 records from Argyll Biological Records Dataset. 2 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 78 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 33 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 910 records from Vegetation data from protected areas in Denmark (? 3 in the Danish Nature Protection Act). 10 records from Merseyside BioBank Active Naturalists (verified). 1 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 1 records from Naturschutzgebiet L?neburger Heide. 71 records from Donn?es naturalistes de Pierre HUGUENY. 1 records from Feuchtbiotop Weidenkaule. 1 records from Tiere und Pflanzen um uns herum !. 1 records from Gemeinde Sursee. 1 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 4878 records from Atlas des plantes vasculaires de Lorraine. 126 records from Ireland's BioBlitz. 1 records from H?hle am Neuweg / S?chsische Schweiz. 1 records from Eschlberg Thalhausen. 1 records from LaBoOb02. 166 records from Chronicle of Nature - Phenology of Plants of Carpathian Biosphere Reserve. 262 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 406 records from Hertfordshire Flora Survey Records 1987-2005. 1 records from Isarufer. 1 records from Sudeniederung (Amt Neuhaus), Landkreis L?neburg. 2 records from vegetation releves on grassland gridplots 2007-2009. 1 records from Lindau im Bodensee. 1 records from Naturpark Sternberger Seenland. 138 records from Biodiversit?tsdatenbank des Landes Salzburg. 2 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 2 records from UCR - University of California, Riverside Herbarium - Vascular Plants. 2 records from Umgebung der Elsa-Br?ndstr?m-Schule (Kr?ckaupark). 1 records from Trockenhang Greinhartsberg Edelfingen. 1 records from Promberg1. 1 records from Mangfalltal. 58 records from CSIC-Real Jard?n Bot?nico-Colecci?n de Plantas Vasculares (MA). 1 records from Sudeniederung (Amt Neuhaus). 3 records from Donn?es naturalistes d'Aur?lien CABARET. 1 records from Hamberger Br?cke / W?rmtal (Pforzheim). 1 records from Waldhusener Moor (L?beck-K?cknitz). 4 records from Donn?es naturalistes de AMBEC Nils. 370 records from Lund Botanical Museum (LD). 1 records from Tiere und Pflanzen am Pfannenbach. 2 records from Kernberge und Umgebung (Jena). 57 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 1 records from Hemmerder Schelk (Unna). 19 records from Fife Nature Records Centre combined dataset. 116 records from SER Species-based Surveys. 2 records from Kl?twald. 785 records from IBF Monitoring of Vascular Plants. 2 records from River Macrophytes Database. 11 records from Donn?es naturalistes de Philippe GOURDAIN (ANVL). 1 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 2 records from Donn?es naturalistes de Stephan DUBEZ. 1 records from Steinbruch Haas Stuttgart-M?nster. 121 records from Inventaires "Mares" Parc naturel r?gional de Lorraine. 1 records from Schulgel?nde des Schulzentrums am Himmelsbarg. 2 records from Botanic Garden of the Finnish Museum of Natural History. 1 records from Ehmkendorf. 1 records from Schulgel?nde Dientzenhofer-Gymnasium (Bamberg). 1 records from Freiburger Netzwerk Artenvielfalt. 10 records from Vascular plant field notes, NTNU University Museum. 1 records from Unser kleines Rasenst?ck/ D?rer-Gymnasium N?rnberg. 1 records from Herbario COFC de la Universidad de C?rdoba: colecci?n general de plantas vasculares. 1 records from H?ltigbaum. 1 records from Wildes Bremer Leben im Park. 1 records from Esp?ces V?g?tales Menac?es de France m?tropolitaine. 1 records from Faberpark (N?rnberg/Stein). 1 records from K?nigstetten. 10 records from Inventaire de la For?t de la Commanderie, Fontainebleau. 2170 records from Shropshire Ecological Data Network database. 2 records from Artenvielfalt am "Gr?nen Band" bei Coburg: 20 Jahre Wiedervereinigung. 2392 records from Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 10 records from Donn?es naturalistes d'Olivier GARGOMINY saisies sous cardObs. 1 records from City of Edinburgh Natural Heritage Service - Historical Records. 1 records from Schriesheimer Steinbruch. 7 records from Inventaire de la flore de Gironde 2014. 251 records from Donn?es 'Flore remarquable' du Parc national des Pyr?n?es. 1084 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 2 records from GEO-Hauptveranstaltung in "Wildtierland". 1 records from Raus in die Natur. 63 records from Welsh Invertebrate Database (WID). 7 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 15 records from Miscellaneous Vascular Plants. 3270 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 7 records from Invertebrate Site Register - England (1738-2005).. 7 records from Masaryk University - Herbarium BRNU. 1 records from Kinder- und Jugendferiendorf des Kreises Gro?-Gerau - Gedern/Ober-Seemen. 1 records from Reusaer Wald. 1 records from Fuldaaue (Stadtgebiet Fulda). 1 records from Einen Tag lang Forscher sein - Die 5c der Erich-K?stner-Schule erforscht das Bachemer Wiesental. 1 records from Golf de Chantilly. 2 records from Schulgel?nde Paul-Gerhardt-Schule-Dassel. 1 records from Naturpark Kottenforst-Ville 16.6.09. 174 records from Isle of Man historical wildlife records 1995 to 1999. 9 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 643 records from Inventaire permanent de la flore du massif armoricain. 2 records from PAMP-tracheo: Vascular plants in Sierra del Mendaur (Navarra, Spain). Undergraduate thesis, C. Garc?a-Zamora. 1 records from GEO-Hauptveranstaltung (Duisburg). 5 records from Ektomykorrhizen auf VIP Schorfheide (Wald). 3 records from TestWat - Macroinvertebrates and macrophytes of freshwater bodies in Flanders, Belgium. 1 records from Naturschutzstation Schmidsfelden. 1 records from BB-Biodiversit?t b. 1 records from Feuchtbiotop Otto-Hahn-Gymnasium. 1 records from Ecological surveys from Bardon Hill undertaken in the period 2000 to 2007. 23535 records from RNF - Donn?es de la F?d?ration des R?serves Catalanes. 2 records from MHA Herbarium: Eastern European collections of vascular plants. 1 records from Freiburger Tag der Artenvielfalt. 1 records from Langes Tannen in Uetersen. 1491 records from Vascular plant diversity in forests. 1 records from Hoher Stein Kallenhardt. 1 records from Observations lors des phases de reconnaissance et d'installation (terrestre) - La Plan?te Revisit?e Corse 2019. 1 records from Sandhofen. 810 records from Flore d'Ille-et-Vilaine. 1 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 4 records from Ty Canol National Nature Reserve (NNR) Species Inventory. 1 records from Wangerooge. 1 records from Nei?etal. 7 records from Inventaire de la flore de Gironde 2017. 1 records from Biosph?re Bliesgau. 11 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 126 records from National Trust for Scotland Species Records. 325 records from Donn?es issues du dispositif de Biosurveillance des Retomb?es Atmosph?riques M?talliques par les Mousses (BRAMM). 1 records from Wanderweg am Windebyer Noor (bei Eckernf?rde). 1 records from Sukzession Industriebrache. 1 records from Inventaire de la flore des Deux-S?vres 2013. 1 records from Feuchtwiese in Langes Tannen (LMS), Klasse 5c. 1 records from Flora und Fauna im Brexbachtal. 2 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 41 records from Vascular Plant Herbarium, UiB. 1 records from Brander Wald (Stolberg). 1 records from Landschaftsschutzgebiet Buchhorst2. 1 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 2 records from Walldorf-Wiesloch: "Natur ?ber den Gleisen". 1 records from FFH-Gebiet Ahrbachtal. 170 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 1 records from Sandloch - H?hle. 1 records from Streuobstwiese Kugelberg (Ulm). 1087 records from The Fungal Collection at the Senckenberg Museum f?r Naturkunde G?rlitz. 484 records from Carnet en Ligne. 1 records from Fuchsloch (Mohlsdorf/Ostth?ringen). 1 records from Am Moosangerweg. 1 records from Bioblitz 2013 Copenhagen Denmark. 46 records from MEL AVH data. 1828 records from Greater London Habitat Survey tree data. 1 records from Altenburg bei Bamberg. 2 records from Inventaire de la flore de Charente-Maritime 2013. 31 records from RNF - Conservatoire d'espaces naturel Nord-Pas-de-Calais. 1 records from Streuobstwiese Stedar. 3 records from Herbario EMMA. Herbario de la Escuela T?cnica Superior de Ingenieros de Montes. UPM. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences